Variabilidad temporal de fósforo y su relación con las avenidas y estiajes de las cuencas hidrográficas del Nanay, Chillón-Rímac-Lrín y Azángaro - Lopez Cardenas, Gonzalo Ernesto (2023)
The concentration of total phosphorus and its level of risk of eutrophication were monitored in surface waters of five rivers in the hydrographic basins of the Pacific (Rímac, Chillón and Lurín), Atlántico (Nanay) and Titicaca (Azángaro) between the years 2011 and 2021. The data were obtained from the National Water Resources Information System (SNIRH), the National Water Authority (ANA) and the National Meteorology and Hydrology Service (SENAMHI). Simple analysis of variance (one-way ANOVA) and factorial analysis (two-way ANOVA) were performed to evaluate the influence of the sampling points (spatial factor) and the hydrological stations (seasonal factor). The analyzes were performed using the SYSTAT 12.0 program. The results determined that the concentration of total phosphorus varied between the hydrographic basins, where the rivers of the Pacific basin had higher average values than the rivers of the Atlantic and Titicaca basins, indicating spatial variability. The concentration of total phosphorus also varied within each river between the sampling points, mainly in the Lurín, Chillón and Rímac rivers, showing a spatial pattern of distribution along the river, whose average values increased in the direction of the lower zone or River mouth. The concentration of total phosphorus also varied temporally between the years 2011 to 2021, mainly in the Chillón, Rímac and Nanay rivers, showing a positive increase in phosphorus content over recent years, evidencing that the temporal variation in the concentration of Total phosphorus was significant in the Chillón, Rímac and Nanay rivers, indicating that there was a positive increase over recent years, despite the fact that the concentration of total phosphorus in the Nanay river was below the permissible limit. On the other hand, the Lurín and Azángaro rivers will not present temporal variation in the concentration of total phosphorus.